Manajemen Rehabilitasi Rawat Jalan Penyalahgunaan Narkoba BNNP Sumut - Septia, Windy; Lestari, Sri; Lestari Nasution, Annio Indah (LPPM Universitas Labuhanbatu, 2022)
The purpose of this study: First, to regulate outpatient rehabilitation of drug abuse and the influence of crime rates in Indonesia at the National Narcotics Agency of North Sumatra Province.Â Second, to carry out the process of planning and monitoring patients who use narcotics at the National Narcotics Agency of North Sumatra Province.Â This type of research is a qualitative approach, which uses interviews and observations conducted by seeking and collecting data related to the management of outpatient rehabilitation.Â The results of the study concluded to move patients to reduce the use of rehabilitated narcotics.